Generation of UHV with Turbomolecular Pump and Dry Backing Pump: Meeting the demand for completely hydrocarbon‐free vacuum. (4th October 2017) - Schopphoff, Andreas; Braunschweig, Falk
Summary: For the generation of ultra‐high vacuum (UHV), multiple pumps and pump combinations are possible. In the past, due to its high compression ratio, the most commonly used backing pump was the oil‐sealed rotary vane pump. But the growing demand for hydrocarbon‐free vacuum makes other solutions necessary: A completely magnetically levitated turbomolecular pump combined with a dry multistage Roots pump is not only able to generate oil‐free UHV pressure but also eliminates contamination due to operating error. Residual gas analyses prove that with this pump combination, the limiting partial pressure of hydrogen can be significantly reduced.